Thoracic scales of moths as a stealth coating against bat biosonar. Issue 163 (26th February 2020) - Neil, Thomas R.; Shen, Zhiyuan; Robert, Daniel; Drinkwater, Bruce W.; Holderied, Marc W.
Abstract : Many moths are endowed with ultrasound-sensitive ears that serve the detection and evasion of echolocating bats. Moths lacking such ears could still gain protection from bat biosonar by using stealth acoustic camouflage, absorbing sound waves rather than reflecting them back as echoes. The thorax of a moth is bulky and hence acoustically highly reflective. This renders it an obvious target for any bat. Much of the thorax of moths is covered in hair-like scales, the layout of which is remarkably similar in structure and arrangement to natural fibrous materials commonly used in sound insulation. Despite this structural similarity, the effect of thorax scales on moth echoes has never been characterized. Here, we test whether and how moth thorax scales function as an acoustic absorber. From tomographic echo images, we find that the thin layer of thoracic scales of diurnal butterflies affects the strength of ultrasound echoes from the thorax very little, while the thorax scales of earless moths absorbs an average of 67 ± 9% of impinging ultrasonic sound energy. We show that the thorax scales of moths provide acoustic camouflage by acting as broadband (20–160 kHz) stealth coating. Modelling results suggest the scales are acting as a porous sound absorber; however, the thorax scales of moths achieve a considerably higher absorption than technical fibrous porous absorbers with the same structural parameters. Such scales, despite being thin and lightweight, constitute a broadband, multidirectional and efficient ultrasound absorber that reduces the moths' detectability to hunting bats and gives them a survival advantage.